Competence of Filipino Secondary Science Teachers in Developing Self-Learning Modules (SLMs) - Auditor, Nessel Dela Pena; Mutya, Romel Cayao (Jurnal Pendidikan Progresif, 2022)
Competence of Filipino Secondary Science Teachers in Developing Self-Learning Modules (SLMs). Objectives: This study investigates the competence of Filipino secondary science teachers in developing SLMs in terms of intellectual property compliance, learning competencies, instructional design and organization, instructional quality, assessment, and readability. Methods: Data were gathered from 68 Filipino teachers using simple random sampling and clustered sampling techniques. To analyze the data, frequency count and percentage, mean and standard deviation, and one–way Analysis of Variance (ANOVA) were utilized. Findings: Results revealed that science teachers were highly competent in developing SLMs across all six variables. Furthermore, there was a statistically significant difference in the competence in developing SLMs in terms of intellectual property compliance based on their highest educational attainment and in terms of the aspects of learning competencies, instructional design, and organization, and assessment based on their sex. Conclusions: Teachers' competence is essential in improving the quality of performance in the learning process. Keywords: new normal education, science education, self-learning modules, teacher’s competence.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202214